Pengujian Black Box pada Aplikasi Pertokoan Minimarket Menggunakan Metode Equivalence Partitioning - Rizky Prasetyo Adi; Yoga Koswara; Jajang Tashika; Yuliana Devi; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2020)
Quality measurements in software are currently required before the software will be used by users. This aims to determine the weakness of the system so that the data generated can match the data entered after the data is executed. This method focuses on data entry, system display, memory usage, and data execution speed so that if the input data does not match what is expected then the system fails.In implementation problems often arise when testers are never sure whether the software being tested has actually passed the test. This happens because there may be several execution paths that have never been tested. The minimarket stock management application will be tested using a black box test where this test is only intended to see if the program matches the function desired by the program without knowing the program code used. To generate test case designs automatically in black box method software testing with the equality.technique partition technique.